What is the Impact of Infrastructure, Information and Communication Technology (ICT), and Economic Stability on Central Java's Economic Growth? - Pardomuan Robinson Sihombing; Ade Marsinta Arsani; Dyah Purwanti; Sigit Budiantoro (Journal of Government and Political Issues, 2023)
This study seeks to examine the impact of Infrastructure, ICT, and Economic Stability on the economic growth rate in Central Java. The data for this research is procured from authoritative sources, namely the Statistics Indonesia (Indonesian: Badan Pusat Statistik, BPS, lit. 'Central Agency on Statistics') and the National Research and Innovation Agency (Indonesian: Badan Riset dan Inovasi Nasional, BRIN). To analyze the data, a multiple linear regression method was employed, utilizing cross-sectional data. The findings reveal that, when considered collectively, all the variables significantly influence Central Java's economic growth. On an individual level, infrastructure, ICT, and economic stability each demonstrate a marked positive correlation with economic growth. Drawing from these insights, the study underscores the imperative for devising comprehensive macro-socioeconomic policies. Such strategic interventions are crucial to ensure that Central Java's economic growth remains both robust and sustainable over time.